Essential Oils: Sources of Antimicrobials and Food Preservatives - Pandey, Abhay K.; Kumar, Pradeep; Singh, Pooja; Tripathi, Nijendra N.; Bajpai, Vivek K. (Frontiers in Microbiology, 2017)
Aromatic and medicinal plants produce essential oils in the form of secondary metabolites. These essential oils are having a diverse way of application in the food system, perfumery, and cosmetics. The use of essential oil as antimicrobial and food preservative agents is of great concern because of several side effects of synthetics. These oils have a potential to be used as food preservative including cereals, grains, pulses fruits, and vegetables. In the current review, we have briefly reviewed the literature and summarizing the uses of essential oils with special emphases on the antibacterial, bactericidal, antifungal, fungicidal and food preservative properties. These essential oils have pronounced antimicrobial and food preservative properties because essential oils consist of various active constituents (terpenes, terpenoids, carotenoids, coumerines, curcumines) with great significance for food industries. Thus, these properties of essentials oils offer a possibility to substitutive natural, safe, eco-friendly, cost-effective, renewable and easily biodegradable antimicrobials for food commodities preservation in near future.